Innovative fisheries extension methodology —its impact on fisheries development in Karnal - Markanday, Jagdish (Indian Farming, 2015)
In the state of Haryana, there was a time when large number ofponds furnished by rainwater lay unutilized. An innovative extensionmethodology used by the scientists in the Karnal district for fishfarming, could convince the village Panchayats and the local people to take up fish farming to earn a good profit by selling these fishes. A training imparted by the scientists to the unemployed local youthscould bring a change in their attitude towards fish farming.